The Effects of Zigzag Ladder Exercise Crossover Shuffle, In Out Shuffle and Ali Shuffle Against Speed and Agility - Pandarwidi S, Afryan; Siantoro, Gigih; Khamidi, Amrozi (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study was to analyze: (1) the effect of the Ladder Zigzag crossover shuffle exercise on speed and agility; (2) the effect of the Ladder In out shuffle exercise on speed and agility; (3) the effect of the Ladder Ali shuffle exercise on speed and agility; (4) differences in the influence of Ladder Zigzag crossover shuffle, In out shuffle and Ali shuffle on speed and agility. This type of research is quantitative with quasi-experimental methods. The research design used is maching only design and data analysis using t-test and ANOVA. Retrieval of data using a sprint 30 meters to measure speed and agility t-test to measure agility at the time of the pretest and posttest. The results showed that the difference between the pretest and posttest of each group were: (1) experimental group I for speed = 0.787 and agility = 0.731 (2) experimental group II for speed = 0.866 and agility = 0.881 (3) experimental group III for speed = 0.863 and agility = 0.84 (4) the control group for speed = 0.115 and agility = 0.118. Based on the above analysis, it can be concluded that there was an increase in speed and agility for each group after being given the Ladder Zigzag crossover shuffle, In out shuffle and Ali shuffle exercises seen from the t-test. In addition, through the ANOVA test, where the Ladder Zigzag crossover shuffle, In out shuffle and Ali shuffle exercises had a better effect than the control group.